How to motivate managers for CSR?: Commitment to CSR by transformational leadership in meetings - Wabitsch, Vanessa Vivian (2014)
Purpose: The aim of this research is to examine how it is possible to continuously motivate managers from different departments for Corporate Social Responsibility (CSR). The goal is to investigate if and how CSR leaders can realize commitment to CSR by conducting meetings in transformational leadership style. Methodology: The study uses a combination of theoretical and empirical research. Theoretical research contracts and contrasts knowledge of the areas CSR, transformational leadership and meetings in new ways. By empirical research qualitative and quantitative data is attained by 12 interviews with CSR leaders and managers of 6 Australian organizations. Findings: Transformational leadership clearly motivates managers for CSR in meetings, because it enhances trust, understanding and commitment to CSR. All of the transformational leadership components are relevant and leaders can enhance them by specific behaviors. The motivational effects of various transformational leadership elements depend on characteristics of the audience such as position, gender, personality and experience. Practical Implications: Leaders already apply the concepts of transformational leadership, but it is recommended to increase its appliance for achieving optimal motivation. For realizing commitment leaders need to be aware of different impacts of transformational leadership elements and emphasize transformational leadership behavior in CSR meetings adjusted to the audience. Limitations: Despite the sample size corresponds to academic standards of qualitative research, there are limitations regarding the investigation of the effects of transformational leadership on different age groups, various industries, organization types or countries.